Algoritmo genético com operador de transgenia para minimização de makespan da programação reativa da produção - Viana, Monique Simplicio (2016)
In recent years, several studies have been carried out to minimize the production time (makespan) in a production schedule of a scenario that represents a manufacturing system. The problem of production scheduling is classified as a combinatorial problem belongs to the NP-hard class of computational problems. Furthermore, in a real world production system, there are many unexpected events (eg, review of production, entry of new products, breaking machines, etc.). To deal with the interruptions of the initial programming, we need to change any settings, which is called reactive production schedule or, simply, reactive scheduling. As a problem of combinatorial features, meta-heuristics is widely used in its resolution. This paper proposes a method that uses an evolutionary meta-heuristic Genetic Algorithm in conjunction with an operator called “Transgenics”, which allows to manipulate the genetic material of individuals adding features which are believed to be important, with the proposal to direct some population of individuals to a more favorable solution to the problem without removing the diversity of the population with a lower cost of time. The objective of this study is to use the Genetic Algorithm with transgenics operator obtain a reactive programming acceptable response time to minimize the makespan value. The objective of this study is to use the Genetic Algorithm with transgenics Operator obtain a reactive programming acceptable response time to minimize the makespan value. Experimental results show the proposed algorithm is able to bring better results than the makespan algorithm and compared in a shorter processing time due to the search direction which provides transgenic operator.